Temporal habitat partitioning and resource competition between congenerics: Testing for density-dependent growth and mortality in estuarine shrimp. - Robert P Dunn; Matthew E Kimball; Bruce W Pfirrmann; Andrew S Bruck; Willa M Lane (PLoS ONE)
Habitat partitioning can promote coexistence of closely related competitors. Two congeneric shrimps (brown shrimp, Penaeus aztecus, and white shrimp, Penaeus setiferus) which utilize estuaries in the southeastern U.S. temporally partition much of their nursery habitat occupancy but also experience a period of overlap at the respective tails of their nursery residency. Throughout nursery residency, when conspecific or congeneric abundance can be high, density-dependent (D-D) processes may alter demographic rates, but the relative importance of the potential biotic interactions occurring in these habitats (e.g., intra- and inter-specific competition, cannibalism, among others) remains underexplored. Here, we documented the periods of nursery habitat use for these two penaeid shrimp species within a representative salt marsh estuary. Next, a set of manipulative laboratory experiments was conducted to test if conspecific or congeneric density, as well as the relative proportions of each species, affect growth and mortality. In three experiments designed to simulate each of the phases of penaeid shrimp nursery habitat use (brown only, brown and white overlap, white only), shrimp were maintained at ecologically relevant densities (12.5-37.5 m-2) and tagged to follow growth trajectories. We found varying degrees of density-dependence between species and across response variables (length, mass, mortality), with the effect of additional species identity varying between white and brown shrimp for all three response metrics. Body size was an important predictor of mortality for both brown and white shrimp, with smaller animals exhibiting higher mortality probabilities. These results suggest that changing environmental conditions could lead to D-D impacts on some demographic rates but not others for these ecologically and economically important species during their estuarine residency.